Public Health Policies' Effects On Disease Control And Prevention (Journal of Namibian Studies : History Politics Culture, 2022)
With the purpose of preserving population health, public health policies shape interventions, laws, and programs that are crucial to the prevention and control of disease. This study looks at how public health policies affect the prevention and control of disease in a number of areas, such as chronic illnesses, infectious diseases, environmental health, and health inequities. This study emphasizes the efficacy of public health policies in lowering the burden of disease, enhancing health outcomes, and fostering health equity through a thorough investigation of policy interventions, implementation methodologies, and health outcomes. This research advances our knowledge of practical approaches to public health issues and provides guidance for evidence-based policymaking aimed at improving population health and well-being by combining data from various contexts and groups.